Novel composite layer and method for producing composite layer
The photocatalytic nanoparticles are generated by flame spray pyrolysis and the composite layer of the permeability network is formed, which solves the problem of insufficient mechanical stability and durability of the existing coating, and achieves a continuous and efficient antimicrobial effect under multiple light irradiation.
Patent Information
- Application Number
- CN202380049342.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-23
- Filing Date
- 2023-06-23
- Publication Date
- 2025-04-04
AI Technical Summary
The existing photocatalytic nanomaterial coatings are prone to lose mechanical stability and durability under light exposure, causing the nanomaterial to detach from the surface and affect the antimicrobial effect.
Photocatalytic nanoparticles are generated in situ by flame spray pyrolysis, and nanoparticle films are formed by aerosol deposition, and then immersed with polymer solution or liquid polymer precursor material to form a composite layer to build a permeation network of photocatalytic nanoparticles in the polymer matrix.
The mechanical stability and durability of the coating are improved, so that the photocatalytic nanomaterials maintain efficient antimicrobial activity after multiple light irradiation cycles.
Smart Images

Figure CN119768453A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a novel composite layer. In particular, the present invention relates to a novel composite layer comprising a percolating network of photocatalytic nanoparticles in a polymer matrix. Furthermore, the present invention relates to a method for producing a composite layer, a use of the composite layer and an article coated with the composite layer.
[0002] Background and Prior Art
[0003] Biofilm is a bacterial colony grown on the surface of medical devices (such as catheters, implants and wound meshes) and is associated with hospital-acquired infections. Therefore, biofilm poses a serious threat to public health and economy, resulting in worldwide morbidity. Biofilm bacteria are usually embedded in endogenously produced extracellular polymers (EPS), which usually contain polysaccharides, proteins, nucleic acids and lipids. Compared with planktonic bacteria, EPS increases the resistance of biofilm to antibiotics by 10 times to 1000 times. Therefore, this high antimicrobial resistance of biofilm has triggered research on the development of new antibiotic-free strategies.
[0004] There are several antibiotic-free strategies for preventing and treating biofilms on medical devices, and one research avenue is to use photocatalytic nanomaterials to try to overcome bacterial antibiotic resistance mechanisms, for example by coating medical devices with photocatalytic semiconductor nanoparticles and destroying bacteria and the corresponding biofilms through the generated reactive oxygen species (ROS) under light irradiation.
[0005] In order for the photocatalytic nanoparticles to impart antimicrobial activity when coated on an article, the generated ROS must be able to leave the surface of the coated article and reach the bacteria / microorganisms so that they can be destroyed. However, currently available coatings have certain disadvantages, such as low mechanical stability and durability of the coating, resulting in the detachment of the nanomaterial from the surface over time, which can lead to toxicity issues in vivo and also result in the coating no longer providing an antimicrobial effect.
[0006] Therefore, there is a need for coatings containing photocatalytic nanoparticles that exhibit antimicrobial activity via ROS production upon irradiation, which coatings show enhanced durability and activity over several cycles to ensure continuous biofilm disruption. DETAILED DESCRIPTION
[0007] The present inventors have surprisingly discovered a method that utilizes the process of in situ generating photocatalytic nanoparticles by flame spray pyrolysis (FSP) and depositing the nanoparticles on a substrate via aerosol deposition to produce a photocatalytic nanoparticle film on the substrate, followed by immersing the photocatalytic nanoparticle film with a polymer solution or liquid polymer precursor material to form a composite layer.
[0008] The process produces a composite layer comprising a percolating network of photocatalytic nanoparticles in a polymer matrix, wherein the composite layer has enhanced durability and remains active after several irradiation cycles, an improvement over currently known coatings.
[0009] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0010] All embodiments of the invention and specific features mentioned herein may be used alone or in combination with any other embodiments and / or specific features mentioned herein (thus describing more specific embodiments and specific features as disclosed herein) without departing from the disclosure of the present invention.
[0011] As used herein, the term "comprising" will have its ordinary meaning in the art, ie, indicating that the components include but are not limited to the relevant features (ie, include, among other things).
[0012] For the avoidance of doubt, the term "comprising" will also include references to components "consisting essentially of" (particularly "consisting of") the relevant materials.
[0013] As used herein, unless otherwise indicated, the term "consisting essentially of shall mean that the relevant component is formed by at least 80% (e.g., at least 85%, at least 90% or at least 95%, such as at least 99%) of the specified substance, according to the relevant measure (e.g., by weight thereof). The term "consisting essentially of" may be replaced by "consisting of".
[0014] Whenever the word "about" is used herein in the context of a quantity, e.g., an absolute quantity, such as weight, volume, size, viscosity, diameter, power, distance, molecular weight, etc., or a relative amount (e.g., percentage) of a single component in a material (including concentrations and ratios), a time frame, and a parameter, such as temperature, etc., it is understood that such variables are approximate and may therefore vary by ±10%, e.g., ±5%, preferably ±2% (e.g., ±1%) from the actual quantity indicated herein. This is true even if such a number is first presented as a percentage (e.g., "about 10%" may mean ±10% with respect to the number 10, i.e., any value between 9% and 11%).
[0015] Production method
[0016] According to one aspect of the present invention, there is provided a method for producing a composite layer in which photocatalytic nanoparticles are embedded in a polymer matrix, wherein the method comprises the following steps:
[0017] a. Provide a substrate;
[0018] b. generating photocatalytic nanoparticles in situ by flame spray pyrolysis and depositing the nanoparticles on the surface of the substrate via aerosol deposition to produce a photocatalytic nanoparticle film on the surface of the substrate; and
[0019] c. immersing the photocatalytic nanoparticle film with a polymer solution or a liquid polymer precursor material to form the composite layer,
[0020] wherein the photocatalytic nanoparticle film has a thickness of about 50 nm to about 5000 nm,
[0021] The method is hereinafter referred to as "the method of the present invention".
[0022] The result of the process of the invention is the production of a composite layer comprising a percolating network of photocatalytic nanoparticles in a polymer matrix.
[0023] The term "composite layer" refers to a composite mixture of a matrix material as a polymer and a filler material as photocatalytic nanoparticles. Since the filler material of the present invention is a nanomaterial, the composite layer can also be called a "nanocomposite material layer". As described below, the composite layer may include two layers, namely a lower layer comprising a nanoparticle film and an upper layer formed by a polymer but without the presence of nanoparticles. Such a composite layer is provided by immersing the photocatalytic nanoparticle film with a liquid polymer precursor material covering the nanoparticle film, and the thickness of the upper layer is determined by the amount of the liquid polymer precursor material covering the nanoparticle film.
[0024] Since the same polymer is used, the upper layer can be considered as part of the entire composite layer, but the thickness of the upper layer should not exceed about 440nm, such as about 50μm to 440nm, for example about 50μm to 360nm, to ensure that the active oxygen species can diffuse away from the surface of the composite layer.
[0025] As used herein, the term "percolating network of photocatalytic nanoparticles" refers to a continuous film layer of nanoparticles deposited on a substrate. In such a network, the deposited nanoparticles are randomly distributed but connected in a manner to form a continuous porous mesh, the pores of which allow the polymer solution / liquid polymer precursor to penetrate into the film.
[0026] In the context of the present invention, the percolation network of photocatalytic nanoparticles is formed by step b) via in situ flame pyrolysis production of photocatalytic nanoparticles and aerosol deposition of the formed nanoparticles on a substrate. Thereafter, a polymer solution / liquid polymer precursor material is added to the surface of the nanoparticle layer formed on the substrate, which penetrates the pores of the percolation network, thereby producing a composite matrix after the polymer solution / liquid polymer has hardened / cured. The network formed by the deposited photocatalytic nanoparticles can also be referred to as a continuous percolation network.
[0027] The inventors have found that such percolation networks are advantageously obtained by the process of the invention and that other commonly known processes for producing nanoparticle films do not necessarily result in such films.
[0028] Flame spray pyrolysis is a well-known technique in the art with good scalability and the ability to tune the properties (size, crystallinity, etc.) of the produced nanoparticles. The advantage of flame spray pyrolysis is that the properties of the nanoparticles can be tuned by controlling process variables such as flame temperature, reactant concentrations, mixing and / or flow rates (Teoh, WY; Amal, R..; L. Flame Spray Pyrolysis: An Enabling Technology for NanoparticlesDesign and Fabrication. Nanoscale 2010, 2(8), 1324).
[0029] The substrate may be placed in the flow path of the flame at a distance of about 5 cm to about 100 cm, such as about 5 cm to about 50 cm, for example about 5 cm to about 30 cm.
[0030] When stating that the substrate is placed in the flow path of the flame, it is meant that the surface of the substrate to be coated is oriented in the flow path of the flame. In particular, the substrate may be oriented so that the surface on which the nanoparticle film is to be deposited is substantially horizontal and facing downwards.
[0031] The thickness of the photocatalytic nanoparticle film can be controlled by the deposition time, and in this regard, the substrate can be placed in the flow path of the flame for a time of about 1 second to about 300 seconds, such as about 1 second to about 250 seconds, such as about 5 seconds to about 120 seconds, for example about 5 seconds to about 60 seconds.
[0032] The nanoparticle film thickness may be from about 50 nm to about 2000 nm, such as from about 150 nm to about 1500 nm, for example from about 150 nm to about 750 nm, in particular from about 150 nm to about 700 nm, such as from about 300 nm to about 600 nm.
[0033] Aerosol deposition of in situ generated nanoparticles may occur by thermophoresis. That is, the substrate surface may be cooled so that the photocatalytic nanoparticles are attracted to and coat the substrate surface. The substrate surface may be cooled by any means, but is preferably held by a water-cooled holder.
[0034] After being deposited on the surface of the substrate, and before adding the polymer solution / liquid polymer precursor material, the photocatalytic nanoparticle film can be stabilized in situ, such as by a flame annealing step. For example, the photocatalytic nanoparticle film can be subjected to an elevated temperature by flame treatment for a set period of time, such as about 5 seconds to about 120 seconds, for example, about 20 seconds to about 40 seconds. In addition, for the annealing step, the substrate can be placed at a distance of about 5 cm to about 20 cm from the flame.
[0035] The photocatalytic nanoparticles may be selected from the list consisting of titanium dioxide nanoparticles, silver-titanium nanoparticles, zinc oxide nanoparticles, iron-titanium oxide nanoparticles, copper-titanium oxide nanoparticles, and mixtures thereof.
[0036] In particular, the nanoparticles are photocatalytically active in the visible light spectrum, and ideally the nanoparticles have a broad absorption band starting at about 400 nm (visible light range) and extending into the near infrared region of the spectrum (such as up to about 1000 nm). Such nanoparticles that can achieve this absorption / activation range include silver-titanium nanoparticles, a material commonly referred to as "black titanium dioxide". The term "silver-titanium nanoparticles" refers to TiO2 nanoparticles that have been doped with silver (Ag) atoms to produce visible light active Ag / TiO x Nanoparticles, including TiO x Often referred to by the term "suboxides". Without wishing to be bound by theory, it is believed that where silver is doped into TiO2 this introduces localized surface plasmon resonance properties into the system and shifts the peak absorption of the nanoparticles from the UV into the visible light activation range.
[0037] The photocatalytic nanoparticles may have an average primary particle size of about 5 nm to about 100 nm, such as about 5 nm to about 60 nm, for example about 10 nm to about 50 nm.
[0038] The term "primary particle size" refers to the average size of each individual nanoparticle crystallite. That is, the primary particle size is the size of each individual nanoparticle separated from other nanoparticles in space, and the technician will understand that nanoparticles can be gathered together to form a cluster, and this does not affect the size of the nanoparticle crystallite size. The crystallite size of nanoparticles can be measured by any term known in the art (e.g., x-ray diffraction (XRD)).
[0039] Before adding the polymer solution, the nanoparticle film has a porosity of about 50% to about 99%, such as about 60% to about 98%. The porosity of the nanoparticle film can be calculated by the mass per unit area and the thickness measured by electron microscopy of the film. Alternatively, the porosity can be measured by correlating the film mass per unit area (obtained by weight analysis) with the film thickness (obtained by cross-sectional SEM images), taking into account the bulk density of the deposited material.
[0040] The skilled person knows how to calculate the porosity of such nanoparticle films and examples can be found in G. Sotiriou et al., Advanced Functional Materials, Flexible, Multifunctional, Magnetically Actuated Nanocomposite Films, Vol. 23(1), 2013, 34-41.
[0041] The thickness of the composite layer can be in a similar range to the nanoparticle film itself, such as about 50 nm to about 2000 nm, such as about 150 nm to about 1500 nm, for example about 150 nm to about 750 nm, in particular about 150 nm to about 700 nm, such as about 300 nm to about 600 nm.
[0042] The amount of polymer solution can be such that the resulting composite layer forms two layers, i.e., a lower layer comprising a nanoparticle film and an upper layer formed by a polymer but without nanoparticles. Since the same polymer is used, the upper layer can be considered as part of the entire composite layer, but the thickness of the upper layer should not exceed about 440 nm, such as about 50 μm to 440 nm, for example about 50 μm to 360 nm, to ensure that the active oxygen species can diffuse out from the surface of the composite layer.
[0043] The substrate may be composed of a material selected from the list consisting of: glass, ceramic, plastic, metal, cross-linked elastomer, and mixtures thereof. For example, the substrate may be a silicon substrate.
[0044] The polymer solution or liquid polymer precursor material can be applied to the nanoparticle film via spin coating, cast coating, slot coating, spray coating or dip coating.
[0045] When applying the polymer solution or liquid polymer precursor material, the substrate may be oriented so that the surface to be coated is in a substantially horizontal and upward position.
[0046] The polymer can be a water-insoluble polymer, optionally wherein the polymer is selected from the list consisting of poly(dimethylsiloxane) (PDMS), poly(urethane), poly(methyl methacrylate) (PMMA), poly(ethylene), poly(propylene), poly(lactic-co-glycolic acid) (PLGA), copolymers of any of these polymers, and mixtures thereof.
[0047] After application of the polymer solution / liquid polymer precursor, the polymer may undergo a heating or curing step. For example, when the polymer is applied in solution form, after application, the layer may be heated to evaporate the solvent, leaving the polymer. Alternatively, when applied as a liquid polymer precursor, it may be applied to a surface and then a curing step may be performed at an elevated temperature, optionally wherein the polymer precursor undergoes crosslinking.
[0048] The composite layer may be formed directly on the surface of the substrate, or the substrate may include a sacrificial coating on which the composite layer is formed, wherein after the composite layer is formed, the sacrificial layer may be removed to obtain a free-standing composite layer film.
[0049] The sacrificial layer may be composed of a water-soluble polymer material, such as a polymer selected from the list consisting of poly(vinyl pyrrolidone) (PVP), polyvinyl alcohol (PVA), poly(ethylene glycol) (PEG), poly(acrylamide), and poly(acrylic acid) copolymers.
[0050] Alternatively, the sacrificial layer may be composed of a water-insoluble material, such as a photolithographic sacrificial layer, for example a polydimethylglutarimide polymer blend.
[0051] The substrate may be provided with an already existing sacrificial layer, or the sacrificial layer may be formed as part of the method of the invention.For example, the sacrificial layer may be formed by coating the surface of the substrate with a polymer solution or liquid polymer precursor material as defined above.
[0052] The sacrificial layer polymer solution / liquid polymer precursor material may be coated on the surface of the substrate via spin coating, cast coating, slot coating, spray coating or dip coating.
[0053] After the composite film is produced on the sacrificial layer, the coated substrate can be immersed in water to dissolve the sacrificial layer, thereby obtaining a free-standing composite layer.
[0054] As used herein, the term "water-insoluble polymer" refers to a polymer having a solubility of less than about 0.1 mg / mL in an aqueous solvent (such as water) at about 25°C. -1 of polymers.
[0055] Composite layers and coated articles
[0056] According to another aspect of the present invention, there is provided a composite layer obtained or obtainable by the method of the present invention.
[0057] Also provided is a composite layer comprising a percolating network of photocatalytic nanoparticles in a polymer matrix, wherein the composite layer has a thickness of about 50 nm to about 5000 nm.
[0058] The composite layer may comprise any of the features of a composite layer as outlined in the method of the present invention.
[0059] The composition layer obtained by the method of the present invention can have a high nanoparticle uniformity with a high nanoparticle content. In this regard, the photocatalytic nanoparticles can be present in an amount of about 2 volume % to about 60 volume % of the composite layer, such as about 10 volume % to about 50 volume % of the composite layer, for example about 20 volume % to about 45 volume % of the composite layer.
[0060] The composite layer may have a thickness of about 50 nm to about 2000 nm, such as about 150 nm to about 1500 nm, for example about 150 nm to about 750 nm, in particular about 150 nm to about 700 nm, such as about 300 nm to about 600 nm.
[0061] The polymer of the polymer matrix can be a water-insoluble polymer, optionally wherein the polymer is selected from the list consisting of poly(dimethylsiloxane) (PDMS), poly(urethane), poly(methyl methacrylate) (PMMA), poly(ethylene), poly(propylene), poly(lactic-co-glycolic acid) (PLGA), copolymers of any of these polymers, and mixtures thereof.
[0062] The composite layer may be composed of two layers, namely a lower layer comprising a nanoparticle film and an upper layer formed of a polymer but without the presence of nanoparticles.
[0063] Since the same polymer is used, the upper layer can be considered as part of the entire composite layer, but the thickness of the upper layer should not exceed about 440nm, such as about 50μm to 440nm, for example about 50μm to 360nm, to ensure that the active oxygen species can diffuse away from the surface of the composite layer.
[0064] The composite layer may be deposited on a substrate, optionally wherein the substrate may be composed of a material selected from the list consisting of glass, ceramic, plastic, cross-linked elastomer, and mixtures thereof.
[0065] The substrate can be a peelable backing layer, such as a plastic peelable backing layer. That is, the composite layer can be deposited on a substrate, which the end user can peel off and apply to another surface to provide photocatalytic disinfection properties, or any of the beneficial properties outlined herein, to the applied surface.
[0066] Alternatively, the substrate can be made of a soluble material, such as a water-soluble or organic solvent-soluble material, which allows the substrate to be dissolved at the end used to release the composite layer. Suitable soluble materials can be selected from the list consisting of poly(vinyl pyrrolidone), poly(vinyl alcohol), poly(styrene), poly(ethylene), poly(urethane), poly(dimethylsiloxane) and mixtures thereof.
[0067] According to another aspect of the present invention, there is provided an article coated with a composite layer as defined herein.
[0068] The coated article can be a medical article, such as a medical tube (e.g., a catheter or endotracheal tube), a respirator, an implant, or a wound mesh. However, in addition to medical applications, the inventors have found that the composite layer can have a wide range of applications, wherein the antimicrobial surface function is advantageous. Therefore, the article can be a surface as a "high-frequency contact object", i.e., an object that is frequently contacted by different members of the public every day and is a source of microorganisms (such as viruses and bacteria) transmission. Exemplary high-frequency contact objects that can be coated by the composite layer include light-emitting display panels (such as automatic teller machines (ATMs)), other public use touch screens, handrails, door handles, etc.
[0069] It is contemplated that the coated article may be obtained by directly coating the article via the method of the present invention, or the composite layer may be provided on a removable backing substrate from which the composite layer may be peeled off and applied to the surface of the article. With regard to this embodiment, the composite layer may include an adhesive layer between the composite layer and the backing substrate, which adhesive layer at least partially remains on the composite layer after peeling off the backing substrate, thus allowing the composite layer to adhere to the surface of the article.
[0070] use
[0071] In another aspect of the invention there is provided the use of a composite layer as defined herein for providing photocatalytic disinfecting properties to a surface.
[0072] The use may be as an antimicrobial coating, such as to provide antimicrobial properties against bacteria and / or viruses.
[0073] In particular, the use may be as an antimicrobial coating, such as an anti-grampositive bacterial coating, for example the use may be as an anti-staphylococcus aureus coating.
[0074] Alternatively, or additionally, the use may be as an anti-gram negative bacterial coating, for example the use may be as an anti-pseudomonas aeruginosa coating or an anti-escherichia coli coating.
[0075] Treatment
[0076] In another aspect of the invention there is provided a method of treating and / or preventing a bacterial infection, such as a wound-related infection or a catheter-related bacterial infection, for example (in both types of infection) Staphylococcus aureus, via the use of a composite layer as defined herein.
[0077] The composite layer may be deposited on the surface of a medical device for use in the treatment and / or prevention of bacterial infection.
[0078] For example, the layer of the composition may be deposited on a surface of a catheter, such as the inner surface and / or the outer surface of the catheter, preferably the outer surface.
[0079] Alternatively, the composite layer may be used alone as a wound dressing or supported on a backing of material suitable for wound dressings, such as gauze, bandage or sponge.
[0080] The method of treatment and / or prevention may include the step of irradiating a coated surface of a medical device (eg, a catheter or a wound dressing) with visible light, thereby generating ROS from the photocatalytic nanoparticles, which impart an antimicrobial effect.
[0081] When the composite layer is on the surface of the catheter, visible light can be provided via an endoscope that has been inserted through the lumen of the catheter to the desired location / depth for illumination.
[0082] For application in wound dressings, light can be delivered externally.
[0083] Any suitable light source (eg, an LED) may be used to illuminate the composite layer.
[0084] The power of the light used can be about 5 mW cm -2 to about 100 mW cm -2 , such as about 10 mW cm -2 to about 75mWcm -2 The irradiation may be performed for about 5 minutes to about 120 minutes, such as about 15 minutes to about 90 minutes.
[0085] As referred to herein, the term "treating and / or preventing" also includes treating and / or preventing biofilm formation on the surface of a material. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] Figure 1 Be the schematic diagram of the various processes of flame aerosol deposition of nanostructured film being presented in single step.Nanoparticle is produced in flame and is deposited on the substrate being positioned above the hot aerosol by water-cooled holder by thermophoresis.Substrate can be the substrate of Si or glass or polymer (for example, polydimethylsiloxane, PDMS) coating.When polymer is injected (for example, by spin coating) on the manufactured film with the polymer of accurate covering nanoparticle film, can produce firm, mechanically stable film.When adding sacrificial layer (for example, polyvinyl pyrrolidone, PVP) on substrate, can make free-standing polymer nanocomposite film.
[0087] Figure 2 (a) STEM-HAADF image and (b) Ag / TiO x EDX element distribution of nanoparticles. (c) Figure 2 Normalized EELS spectra extracted from regions A and B in a. (d) Ag / TiO x High magnification HRSTEM image of the nanoparticles showing Ag and TiO on the produced nanoparticles. x (e) Flame-prepared TiO2 (black line) and Ag / TiO with different Ag contents. x XRD pattern of nanoparticles. (f) Ag / TiO x Ti 2p XPS spectra of the particle films.
[0088] Figure 3 (a) Ag / TiO with deposition time x The film thickness of the film. The inset is t d =30s and t d = 60s Ag / TiO x Cross-sectional SEM images of the nanocomposite films. (b) Ag / TiO x Cross-sectional SEM images of polymer nanocomposite films. (c)(i)t d =5s Ag / TiO x Granular film, (ii) t d =30s Ag / TiO x Granular film, and (iii) Ag / TiO x AFM images of polymer nanocomposite films.
[0089] Figure 4 (a) Ag / TiO xUV-Vis diffuse reflectance spectra of (50% Ag / Ti, gray line) and TiO2 nanoparticles (black line). Inset is (ahv) 1 / 2 (b) Ag / TiO under visible light irradiation x Granular film (solid triangle), Ag / TiO x -Photocatalytic degradation of MB by polymer nanocomposite films (grey squares), TiO2 particle films (open triangles), and pure MB (black squares). (c) Inhibition of MB degradation by Ag / TiO2 by NBT after 30 and 90 min of visible light irradiation (λ = 400 nm-600 nm). x Particles (black columns) and Ag / TiO x Superoxide radical formation measured on polymer nanocomposite (red bars) films. Applied irradiance: 74 mW cm -2 .
[0090] Figure 5 (a) Variation of the thickness of the composite film with a thickness of about 360 nm Ag / TiO under visible light irradiation x Logarithmic reduction (CFU mL-1) of the particle film on Staphylococcus aureus bacterial biofilm. (b) Ag / TiO x Log reduction (CFU mL-1) of Staphylococcus aureus bacterial biofilm by particle film (about 360 nm). (c) Ag / TiO x Granular film (black column) and Ag / TiO x - Recyclability of polymer nanocomposites (red bars) against Staphylococcus aureus bacterial biofilm (tir = 15 min, irradiance = 74 mW cm-2). (d) Ag / TiO x - Log reduction of polymer nanocomposite films against different bacterial strains (Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus). Each data point represents the mean of three biological replicates (three technical replicates were performed for each biological replicate). Error bars represent the standard deviation of these biological replicates.
[0091] Figure 6 (a) Cell viability setup for direct and indirect contact. Cell viability determined by resazurin assay as a function of Ag / TiO x Granular film (black column) and Ag / TiO x Measurement of cytotoxicity of polymer nanocomposites (red columns) in (b) direct and (c) indirect contact with A549 cells for 24 h. Cytotoxicity of TiO2 particle films, TiO2 polymer films, Si substrates, and PDMS-coated substrates are also presented. Error bars are calculated as standard error of the mean (n=3).
[0092] Figure 7 Schematic diagram of flame aerosol deposition and mechanical stabilization (in situ annealing) of a nanocomposite layer on a silicon substrate, outlining the illumination of the film by visible light for antimicrobial purposes.
[0093] Figure 8 It shows that with Ag / TiO x XRD pattern of the as-deposited film prepared by the method of the present invention compared with the nanoparticles.
[0094] Fig. 9 A schematic diagram of polymer film formation is shown.
[0095] Fig.10 SEM images of the nanoparticle film before (10a) and after (10b) annealing are shown, highlighting that the film retains its high porosity even after the annealing step.
[0096] Fig.11 The photocatalytic activity of the composite film when deposited on a Si substrate is shown.
[0097] Fig.12 It shows that Ag / TiO x Representative initial absorbance shift spectra of NBT of the particle film and its polymer nanocomposite after 30 min and 90 min of visible light irradiation.
[0098] Fig.13 The fluorescence intensity spectrum of the aminophenylfluorescein free radical reporter is described in detail. Fig.13 ), which showed no evidence of OH radical formation once visible light irradiation was stopped.
[0099] Fig.14 The assessment of biofilm growth on top of the membrane using the crystal violet method is described in detail.
[0100] Fig.15 SEM images of the composite films are shown.
[0101] Fig.16 a) Evaluated Ag + Ion release ( Fig.16 a) and the effect of applied light dose alone (ie, without nanoparticles), and b) show that the change in biofilm killing over irradiation time is negligible.
[0102] Fig.17 The log CFU reduction of the nanocomposite films (solid bars) after 15 min and 90 min of visible light irradiation is shown, wherein the polymer-infused film maintained its anti-biofilm activity through log CFU reduction even after its fourth cycle, while the nanoparticle film (open bars) significantly lost its activity after the third cycle due to nanoparticle removal during the washing step.
[0103] Fig.18 SEM analysis confirmed Fig.17 The results are shown in Figure 2 for nanoparticle removal.
[0104] Example
[0105] Nanoparticle synthesis and film deposition
[0106] The flame spray pyrolysis (FSP) reactor is used to generate a 5×5 mm substrate mounted on a water-cooled substrate holder. 2 Ag / Ti was synthesized and in situ deposited on a Si substrate of 100 μm. Different concentrations of Ag / Ti (in wt%), such as 5%, 10%, 20%, 30% and 50%, were used in the synthesis of the nanocomposite films, and the photocatalytic best film with a Ti content of 50 wt% was selected for further study. The precursor solutions of Ti and Ag were fed into the FSP.
[0107] Silver acetate (Sigma-Aldrich, purity>99%) and titanium isopropoxide (TTIP, Aldrich, purity>97%) were diluted in a 1:1 mixture of 2-ethylhexanoic acid (Aldrich, purity>99%) and acetonitrile (Aldrich, purity>99.5%), with a total metal (Ti and Ag) concentration of 0.16M. The solution was supplied by a FSP nozzle at a rate of 8mL / min, and oxygen was supplied at a rate of 5L / min (pressure drop 1.5 bar) to disperse it into a fine spray. The substrate holder was placed 20cm above the burner for nanoparticle deposition, and different deposition times of 5s, 15s, 30s and 60s were used to affect the thickness of the nanoparticle film. These films were mechanically stabilized by in-situ annealing 30s with an impingement flow of particle-free ethanol spray at a constant height of 15cm above the burner. The flow rates of the dispersed oxygen and ethanol feeds were 3L / min and 12mL / min, respectively. The nanoparticles thus prepared were collected by a vacuum pump onto a water-cooled glass fiber filter placed 77 cm above the flame. Schematic diagram of the flame aerosol deposition and mechanical stabilization (in situ annealing) of the nanocomposite layer on the silicon substrate is shown in Figure 7 Shown in.
[0108] For comparison, TiO2 films were also prepared as follows: TTIP (Aldrich, purity >97%) was diluted in xylene at a concentration of 0.5 M. The solution was supplied through the FSP nozzle at a rate of 5 mL / min and mounted on a 5×5 mm2 substrate holder. 2The nanoparticles were dispersed into a fine spray on a Si substrate with an oxygen flow of 5 L / min (pressure drop 1.5 bar). The substrate holder was placed 20 cm above the burner for nanoparticle deposition. Thereafter, an annealing step for stabilizing the nanoparticles was performed as described above. The deposition time varied from 15 s to 60 s.
[0109] Figure 2 a shows Ag / TiO x High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of (50% Ag / Ti) nanoparticles. The nanoparticles exhibit agglomerated / aggregated morphology characteristic of flame-prepared nanoparticles, while the Ag nanoparticles appear to be larger than the TiO x Nanoparticles are brighter (Z contrast). Scan Figure 2 Selected area (yellow square) in a to obtain simultaneous hyperspectral data cubes of energy dispersive X-ray (EDX) spectroscopy and monochromatic electron energy loss spectroscopy (EELS). Figure 2 b shows a false color composite of the elemental distribution of O, Ti, and Ag obtained from the EDX spectrum. Figure 2 The Z contrast observed in a clearly confirms that TiO x and the presence of Ag nanoparticles. However, EDX and Z-contrast imaging cannot distinguish the Ti-suboxide phases because they have almost the same composition. Therefore, we consider the simultaneously acquired monochromatic EELS spectra, such as Figure 2 c. These spectra are shown in boxes A and B (see Figure 2 a) by integrating the spectrum from the hyperspectral data cube, subtracting the pre-edge background, and then deconvolving the spectrum with the simultaneously acquired low-loss EELS spectrum (also integrated on the same box). The EELS experiment was configured to record the Ti L2,3 edges with an energy resolution of about 220 meV, allowing detailed studies of the transitions of Ti 2p1 / 2 and 2p3 / 2 electrons to unoccupied 3d orbitals. These edges have been extensively studied with EELS and it is well established that fine structural features can be used to distinguish different TiO x polymorphs. In anatase, the oxygen octahedra around the Ti metal atom are slightly deformed, reducing the perfect Oh point group symmetry to D2d. This results in a slight splitting of the peak corresponding to the transition of the Ti 2p3 / 2 electron to the unoccupied eg state, which itself is caused by the crystal splitting. This can be experimentally resolved as a shoulder on the eg peak located at 460.3 eV, which can be seen in Figure 2 Seen in c (black arrow). Figure 2 The two integrated spectra shown in c are selected from the spectral image ( Figure 2a) to highlight the differences in this feature due to the different TiOx particles captured in the experimental field of view. The spectrum from region A has a striking similarity to anatase, while the spectrum from region B does not correspond well to other EELS spectra reported in the literature. This suggests that the spectrum from region B arises from a less studied Ti-suboxide phase.
[0110] Anatase and suboxide TiO x The mixing of phases is also achieved through Figure 2 The high-resolution HAADF-STEM image shown in d confirms this. Although this image was acquired from a different area of the sample, the HAADF detector was configured to Figure 2 The detectors in a are identical, allowing us to deduce regions of higher pixel intensity corresponding to the presence of Ag nanoparticles. x It is more important to observe multiple lattice planes in the particles. Based on local fast Fourier transform, we observed two These indices are closer to the (010) and (01 - 0) lattice plane. We also observe a plane with a distance The particles are different from those in anatase (020) and (02 - 0) lattice planes correspond well. These particles are Figure 2 d are marked accordingly.
[0111] like Figure 2 As shown in e, Ag / TiO with different Ag contents x Powder X-ray diffraction (XRD) analysis of the nanoparticles also detected Ti-suboxides. For pure TiO2 nanoparticles (black), the peaks in the XRD pattern correspond to the characteristic anatase (JCPDS 021-1272) and rutile TiO2 phases (JCPDS 021-1276), which is consistent with the literature. However, with the increase of Ag content, the XRD pattern shows two significant changes.
[0112] The peaks corresponding to Ag appear at 20° at about 38° and 44°, indicating the presence of metallic Ag nanoparticles. In addition, with the increase of Ag content, the peaks at 33° (attributed to Ti3O5), 28.5° and 29.5° (attributed to Ti4O7 or other suboxide layers such as Ti x O 2x-2 ) with increasing intensity. Similar features have been reported for Ti3O5 and Ti4O7 layers in the Ag / Pt / TiO2 system, which are indicative of SMSI. Our results suggest that in Ag / TiO with Ag / Ti ratios >20%, SMSI xDuring the flame synthesis of the nanoparticles, such Ti-suboxide formation became even stronger, with the 50% Ag / Ti sample having the highest content of TiO x Due to the high temperature during in-situ flame annealing, the XRD pattern of the as-deposited film with the same composition as the 50% Ag / Ti sample looks similar to that of Ag / TiO x Nanoparticles ( Figure 8 ), and Ag / TiO x Compared with the nanoparticles, the anatase content is slightly lower and the Ag particle size is larger. In order to further characterize the produced Ag / TiO x To investigate the formation of Ti-suboxide species in the nanoparticles, we performed X-ray photoelectron spectroscopy (XPS) on 50% Ag / Ti samples deposited as films. The Ti 2p XPS spectra of the Ag / TiOx nanocomposite films (combined with Gaussian fitting) are shown in Figure 2. Figure 2 f. The binding energies at 456.9 eV and 459.1 eV are respectively attributed to Ti-suboxide (Ti 3+ ) and TiO2(Ti 4+ ).
[0113] Ag / TiO x - Fabrication of polymer nanocomposite films
[0114] In order to prepare Ag / TiO x -Polymer nanocomposite films, polymer-coated substrates (76×52 mm) were prepared prior to deposition of nanoparticles 2 More specifically, commercially available PDMS ( 184) A solution of 10 wt % PDMS: acetonitrile: curing agent: 12.68 wt %: 1 wt % was first stirred at 100 rpm. -1 -500rpm s -1 Spin coating for 10 s, then at 1000 rpm s -1 -4000rpm s -1 The glass slide used as the substrate was coated with a PDMS polymer (polydimethylsiloxane) layer by spin coating for 50 s. This step was followed by curing the PDMS on a hot plate at 100 °C for 2 h. As described above, the Ag / TiO x Nanoparticle deposition was performed in situ in the FSP reactor. For nanoparticle deposition, the substrate holder was placed 20 cm above the burner and the deposition time was 15 s. In situ flame annealing was performed 20 cm above the burner using a particle-free xylene flame under cooling conditions. A 1 wt %: 12.68 wt %: 1 wt % solution of PDMS: acetonitrile: curing agent was first heated at 100 rpm. -1 -500rpm-1 Spin-coat onto the existing nanocomposite film for 10 s and then heat at 1000 rpm. -1 -4000rpm -1 The nanoparticles were stabilized on the polymer layer by spin coating onto the existing nanocomposite film for 50 s, followed by curing of the PDMS at 100 °C on a hot plate for 2 h. Fig. 9 A schematic diagram of polymer film formation is shown.
[0115] To remove the polymer film from the substrate, a sacrificial layer of water-soluble polyvinyl pyrrolidone (PVP) film was applied before the first PDMS layer was applied. The film on the substrate was immersed in milli-Q H2O, and then the nanocomposite polymer film was separated and removed with tweezers within 5 min of immersion. The polymer nanocomposite film was cut into 6×6 mm pieces using a 3D printed holder and a glass cutter. 2 The film.
[0116] Nanoparticle and membrane characterization
[0117] Using Cu Kα1 radiation X-ray diffraction (XRD) patterns of the films and collected nanoparticles were performed by a Rigaku MiniFlex diffractometer. Film thickness was estimated by scanning electron microscopy (SEM) with a focused ion beam (gallium source) using a FEI Nova 200 dual beam system. STEM, monochromatic EELS, and EDX experiments were performed on a double aberration corrected Themis Z microscope (Thermo Fisher) operating at 300 kV. The instrument was equipped with a monochromator that was excited and tuned to an energy resolution of 220 meV to obtain Figure 2 EELS results shown in . A SuperXEDX detector (Thermo Fisher) and a Quantum Gatan image filter (Gatan, Inc.) operating in dual EELS mode were simultaneously operated to acquire Figure 2The hyperspectral data set presented in . Spectral experiments were performed using a probe current of 420pA, a convergence angle of 21.4mrad, and a collection angle of 23mrad, while a probe current of 70pA was used for HRSTEM. Atomic force microscopy (AFM) images were recorded with a Bruker DimensionIcon microscope. X-ray photoelectron spectroscopy (XPS) was performed using a Physical Electronics (PHI) system equipped with PHIQuantera II. A 300W xenon lamp (Max 350, AsahiSpectra) equipped with a UV-Vis mirror module (300nm-600nm) was used as a light source. Visible light irradiation (λ=400nm-600nm) was performed using a 25mm long pass filter (>400nm) (Asahi Spectra). Light was delivered to the sample by a quartz light guide equipped with a quartz collimator.
[0118] Flame aerosol nanoparticle deposition on substrates facilitates fine control of the thickness of the deposited nanoparticle film by simply controlling the deposition duration. x The film thickness was determined for the sample with the highest Ti-suboxide content (50% Ag / Ti) at various deposition times (t d ), i.e. 5s-60s.
[0119] Estimation of Ag / TiO from cross-sectional SEM images x Film thickness. Figure 3 a shows the change of deposition time t d The deposition time increased from 5s to 60s to make Ag / TiO x The film thickness increases from about 180 nm to about 1200 nm. d =30s and t d = Ag / TiO at 60s x The cross-sectional SEM images of the membrane are shown in Figure 3 The inset in a highlights their porous structure.
[0120] The structural stability of the deposited nanoparticle films was enhanced by an in situ flame annealing step ( Fig.10 ), while the films retain their high porosity even after the annealing step. Their porous structure allows the infusion of polymer solutions during spin coating, thus forming polymer nanocomposite films. By controlling the polymer concentration and spin coating conditions, a polymer layer with the same thickness as the nanoparticle film can be added to the Ag / TiO x On the surface of nanoparticle film. Figure 3This results in a polymer nanocomposite film with a minimal polymer layer on top of the deposited nanoparticles, as shown in b. The top polymer (PDMS) layer precisely covers the porous nanoparticle film.
[0121] Figure 3 c shows that for (i)t d = 5s and (ii) t d = 30s Ag / TiO deposited on Si substrate x AFM images of the three-dimensional (3D) structure of the film (50% Ag / Ti). The measurement was performed in an area of 5 μm × 5 μm, and in both cases, Ag / TiO x Dense distribution of nanoparticles. Ag / TiO x The roughness of the film (t d =5s) does not exceed 230nm, and large particles are observed on the surface. The surface roughness increases with longer deposition time (e.g., t d =30s). In contrast, Figure 3 The surface of the polymer-infused film shown in c(iii) is significantly smoother than the corresponding particle film due to the presence of a thin PDMS layer that barely covers the nanoparticle film.
[0122] Estimation of band gap energy
[0123] UV-Vis diffuse reflectance spectra were recorded in the wavelength range of 300 nm-800 nm using a UV-Vis spectrophotometer system Specord 210 Plus (Analytik Jena) equipped with an integrating sphere assembly. Band gap energy (Eg) values were calculated using the Kübelka-Münk equation.
[0124] Evaluation of photocatalytic activity
[0125] Methylene blue (MB) is an organic azo dye commonly used as a model molecule to study the performance of photocatalysts. MB degradation experiments were performed at 298 K. Typical MB degradation involves Ag / TiO x Nanocomposite films or Ag / TiO x-polymer film, and the photocatalytic reaction was carried out in a well plate. The pH of MB was adjusted to 9.0 using NaOH, and 2 mL of the solution was added to the well plate containing the membrane. Before irradiation, the mixture was kept in the dark for 30 min to reach adsorption equilibrium on the semiconductor surface. During the photocatalytic reaction, a standard amount of sample (500 μL) was taken out from the reactor at specific intervals. The decolorization of MB was determined by monitoring the change in light absorption at 660 nm using a Specord 210Plus UV-Vis spectrophotometer operating in the wavelength range of 400nm-700nm. The samples were measured in a 3mL quartz cuvette with a light path of 1 cm. Based on the standard curve of concentration and absorption, the C / C0 value representing the decomposition efficiency was calculated. Each experiment was performed three times. For comparison, pure TiO2 film or polymer TiO2 film was used as a reference photocatalyst film under visible light. As mentioned above, two Ag / TiO x Recyclability of nanoparticle films.
[0126] Figure 4 a shows Ag / TiO x Diffuse reflectance ultraviolet-visible (UV-Vis) spectra of nanoparticles (50% Ag / Ti, gray line) and pure TiO2 (black line). In the visible light range, pure TiO2 nanoparticles have almost no absorption, while Ag / TiO x The nanoparticles exhibit broad absorption bands. For both samples, the absorbance at wavelengths < 350 nm is attributed to the anatase phase. In addition, for Ag / TiO x A broad absorption band starting at -400 nm (visible range) and extending into the near-infrared region of the spectrum was observed. This enhanced absorption band is attributed to the surface Ti 3+ Both the formation of centers and the plasmonic properties of Ag nanoparticles.
[0127] In a similar TiO x The introduction of lattice disorder in the system narrows the light band from 3.2 eV to 1.54 eV, which is similar to the visible light absorption band; therefore, the photocatalytic ability is enhanced in this range. Figure 4 The inset in a shows the pure TiO2 and Ag / TiO x Tauc curve of nanoparticles. Pure TiO2 and Ag / TiO x The band gap of the nanoparticles (E g ) values are 3.22eV and 2.88eV respectively. g This change may be attributed to the surface Ti 3+ states and the generation of sub-bandgap energy tails from the distorted Ti-suboxide layer.
[0128] MB degradation assay to investigate Ag / TiO x Granular film (t d = 15 seconds, 50% Ag / Ti) at about 360 nm visible light photocatalytic properties and the corresponding polymer-infused films. For comparison, the photocatalytic efficiency of pure TiO2 particle films with similar thickness and MB without any sample (only irradiation) was also studied. Figure 4 b shows the results of continuous visible light (400 nm-600 nm) irradiation (74 mW cm -2 ) for up to 90 min at Ag / TiO x Particles, Ag / TiO x - Normalized MB concentration (C / C0) of aqueous solutions of polymer nanocomposites and pure TiO2 particle films. Ag / TiO x The particle film (solid triangles) was highly active for MB degradation under visible light (28 min half-life), with >80% of MB degraded within 90 min of irradiation. In contrast, the pure TiO2 particle film (open triangles) showed less catalytic efficiency under visible light irradiation (11% MB degradation at 90 min irradiation). In similar systems, the presence of Ag on the TiO2 surface may enhance MB degradation under visible light; however, the Ag / TiO2 used in this study x The film exhibits significantly stronger photocatalytic activity due to the presence of the Ti-suboxide layer. x The photocatalytic activity of aqueous solutions showed similar results, indicating that the nanoparticles retain their photocatalytic properties when deposited on Si substrates ( Fig.11 ).
[0129] Ag / TiO x -Polymer nanocomposite films also showed high MB degradation efficiency under visible light irradiation, with a half-life of 24 min and MB degradation of about 90% within 90 min. This confirms that the Ag / TiO x The presence of a thin PDMS layer on top of the nanoparticle film did not affect ROS generation and ROS permeability through the PDMS layer. In fact, ROS permeability through PDMS depends on the thickness of the layer. Here, we prepared another polymer Ag / TiO x Nanocomposite film, the thickness of its PDMS layer is about 800nm and about 1200nm.These films do not show photocatalytic properties (data not shown), thus confirming the dependence of ROS permeability on the thickness of the PDMS layer.Therefore, it is critical that the PDMS layer only barely covers the nanoparticle layer to maintain the photocatalytic activity of the nanoparticle film, and the upper limit of 440nm seems to be applicable to the situation where the limited effect on ROS permeability is observed.Above this level, permeability is affected.
[0130] To identify ROS generated in the photocatalytic coating, nitroblue tetrazolium (NBT) was used as an organic molecule reporter. x Superoxide radicals (O2 ·- ) production. O2 was quantified by measuring the absorbance of NBT ·- In the presence of , NBT is reduced to diformazan. Figure 4 c shows Ag / TiO x The NBT absorbance shifts of the particle films and their polymer nanocomposites after 30 and 90 min of visible light irradiation were estimated to be 24% and 42%, respectively (representative initial spectra at Fig.12 Ag / TiO x -The absorbance change (in percent) of NBT in the polymer nanocomposite film after 30 min and 90 min of visible light irradiation is higher than that in the particle film. Fig.13 ) showed no evidence of OH radical formation after visible light irradiation.
[0131] Identification of ROS
[0132] The superoxide anion (O2) was generated through the nanocomposite membrane using nitroblue tetrazolium (NBT) absorption method. ·- ). NBT solution (5 μmol) was prepared in milli-Q water. The nanocomposite film was placed in a 12-well plate and 2 mL of the working solution was added at each position. The resulting solution was irradiated for 30 min and 90 min. NBT has an absorption peak at 260 nm and its absorbance is obtained in the range of 230 nm-300 nm. The generation of free radicals was averaged in three independent experiments.
[0133] Ag-TiO x Antibiofilm activity of particle and polymer nanocomposite films under visible light irradiation Evaluation of Ag / TiO x Antibiofilm activity of nanocomposite films against Gram-positive Staphylococcus aureus (ATCC29213) bacteria. Bacteria were pre-cultured in nutrient broth at 1:500 and diluted to 10 8 The membranes were sterilized at 210°C for 2 h and placed on a well plate. Then, 1.8 mL of the bacterial suspension was added to the wells of a 12-well plate, each well containing one sterilized membrane. The samples were incubated at 37°C for 24 h for bacterial growth. The biofilm growth on top of the membrane was assessed using the crystal violet method ( Fig.14). After incubation, the film was washed twice in phosphate buffered saline (PBS) to remove all planktonic bacteria from the sample. Three parallel tests were performed in the experiment to ensure accuracy. The film was placed in a new well plate, 1 mL PBS was added to each plate, and the film was irradiated with visible light. The intensity of the light reaching the film was measured with a power meter (Thorlabs). After formulating the irradiation time (15 min, 30 min, 60 min and 90 min), the nanocomposite film and solution were vortexed and ultrasonicated in 1 mL PBS to break away from the biofilm.
[0134] The resulting suspension was serially diluted and the suspension was plated on agar plates and incubated at 37°C for 20 h to determine the CFU (see Figure 7 Ag / TiO x Schematic diagram of the biofilm experiment with nanocomposite membranes). A control sample containing a silicon substrate but no nanocomposite membrane was also tested. -2 -74mW cm -2 The effect of applied light dose on the antibiofilm activity of the membranes was also studied over a range of doses.
[0135] Similarly, Ag / TiO x – Anti-biofilm capacity of polymer nanocomposite membranes against Gram-positive Staphylococcus aureus (ATCC29213) and Gram-negative Pseudomonas aeruginosa and Escherichia coli. A control sample containing a PDMS layer without a nanocomposite membrane was also tested. The CFU counts on the samples were averaged and the antimicrobial activity was calculated on a log reduction scale.
[0136] Cell culture and cytotoxicity assessment
[0137] Human A549 cells (lung adenocarcinoma epithelial cell line) (ATCC CCL-185) were cultured in DMEM (GIBCO) containing 10% FBS (GIBCO) and 50U / mL penicillin-streptomycin (ThermoFischer). For Si substrates, cells were grown until 90% confluence and 15,000 cells were seeded into 48-well plates (Sarstedt) in 300 μL of culture medium. The cells were incubated for 16 h and washed with PBS. Then, 400 μL of culture medium was added. For direct contact assays, the test substrate was gently placed into the well with the coated side facing down. For indirect contact assays, the test substrate was placed in a 3D-printed well insert. Since the size of the glass substrate is larger than that of the Si substrate, the protocol was adjusted for the glass substrate. The custom 3D-printed well insert was placed in a 24-well plate (Sarstedt) to leave a size of 8.5×8.5 mm from the well plate plastic. 2The center square of for cell adhesion. For cell attachment, 355 μL of culture medium containing 30,000 cells was incubated for 16 h. The cells were washed with PBS and 355 μL of fresh culture medium was added to the wells. The substrate was placed directly on the cell monolayer or suspended in the culture medium above the cells in the 3D printed insert. After incubation with the substrate for 24 h in both cases, the substrate (and well insert) was removed, resazurin was added, and the plate was incubated for another 4 h. Then 200 μL of culture medium was transferred from each well to a 96-well plate. In addition, fluorescence was measured using an LS55 luminescence spectrometer (Perkin Elmer) with an excitation wavelength and an emission wavelength of 540 nm and 590 nm, respectively. All incubation steps were performed at 37 ° C and 5% CO2. The standard trigonometric language file for 3D printed parts is provided in SI. 3D printing was performed using a photon 3D printer (Anycubic) with a transparent PrimaCreator value resin (Prima Printer Nordic AB).
[0138] To investigate biofilm disruption triggered by visible light irradiation, we incubated particle films with Staphylococcus aureus, a common pathogen in catheter-related infections. Biofilms were grown in the dark for 24 h and illuminated with visible light (15 mW cm -2 -74mW cm -2 ) for 15-90 min. The bacteria still present in the biofilm were then recovered and counted by the number of colony forming units (CFU) per milliliter of sample (CFUs mL -1 ) to quantify these bacteria. Figure 5 a shows the Ag / TiO films with different film thicknesses under visible light irradiation for 15 min and 90 min. x Log reduction of Staphylococcus aureus on particle membrane (CFUs mL -1 ). With the increase of Ag / TiO x The CFU of S. aureus was significantly reduced with increasing film thickness and irradiation time (from 15 to 90 min). The antibiofilm activity of films with thicknesses of approximately 360 nm to 1210 nm was very similar at all irradiation durations, with up to a 2-log reduction in CFU. However, the thinnest films showed the least antibiofilm activity, which may be due to partial surface coverage of the substrate, as confirmed by SEM analysis ( Fig.15 ).like Figure 5 As shown in b, for a film sample with a thickness of about 360 nm, the effect of visible light dose on the Ag / TiO x Effect of visible light dose on the anti-biofilm activity of the particle film. It can be seen that the anti-biofilm activity increases with the increase of visible light dose. Figure 5 b (inset) also shows the data for quantifying CFUs mL-1 It should be noted that Ag + Ion release ( Fig.16 a) and the effect of light dose applied alone (i.e., without nanoparticles) on biofilm killing was negligible ( Fig.16 b).
[0139] Polymer-infused Ag / TiO x Triggered antibiofilm activity of nanocomposite films. Ag / TiO x Particles and Ag / TiO x The log CFU reduction of the nanocomposite membrane against Staphylococcus aureus biofilm was Figure 5 c. Similarly, the log CFU reduction after 90 min of visible light irradiation was Fig.17 During the first cycle, the polymer-infused Ag / TiO x The membranes showed similar or even slightly better anti-biofilm performance. However, the polymer-infused membranes retained their anti-biofilm activity even after their fourth cycle, whereas the nanoparticle membranes significantly lost their activity after the third cycle due to nanoparticle removal during the washing steps, which was also confirmed by SEM analysis ( Fig.18 ). This confirms that a thin PDMS layer on the nanoparticle film (i.e., a layer on top of the nanoparticle film that does not contain nanoparticles) increases the stability and durability of the film and that it maintains their antibiofilm activity over several cycles, with the optimal thin PDMS layer being no larger than 440 nm, and a lower limit of 50 μm being ideal for achieving stability and durability. Polymer-infused Ag / TiO x The triggered anti-biofilm activity of the nanocomposite films against Escherichia coli and Pseudomonas aeruginosa bacterial biofilms was compared with their activity against Staphylococcus aureus biofilms, presenting their log CFU reduction ( Figure 5 d), indicating that the generated ROS have the ability to destroy biofilms from different microorganisms.
[0140] Aq / TiO x Biocompatibility of membranes
[0141] When designing any coating for biomedical applications, characterization of its biocompatibility should be considered fundamentally. It is well known that Ag nanoparticles exhibit significant cytotoxicity, whereas non-irradiated TiO2 is relatively biocompatible. x The cytotoxicity of the nanocomposites and polymer films was determined in two assays on the lung epithelial cell line A549, i.e., direct contact and indirect contact (e.g., simulating direct exposure to an endobronchial tube) ( Figure 6a), as described above in the section entitled “Cell Culture and Cytotoxicity Assessments.” These should assess intrinsic cytotoxicity due to direct contact of particles and polymer membranes with cells and substances leached from the membrane into the cell culture medium, respectively.
[0142] Figure 6 b, c show TiO2 and Ag / TiO x Cytotoxicity results of membranes (both particles and polymer nanocomposite membranes) in direct and indirect contact with A549 cells for 24 h (Si and PDMS served as controls). First, the PDMS layer did not particularly affect cell viability, which corresponds well to its biocompatibility. Neither pure TiO2 particles nor polymer membranes showed cytotoxicity in both direct and indirect contact. Despite relatively mild cell viability >80%, Ag / TiO x The particle film showed the highest cytotoxicity; however, this effect was completely attenuated by PDMS infusion and polymer nanocomposite fabrication. x The surface biocompatibility of Ag / TiO2 films was enhanced in the presence of particles, and the best surface biocompatibility was observed when the composite layer had an outer surface without exposed nanoparticles, i.e., when there was an upper layer containing only PDMS. x The slightly higher cytotoxicity of the membranes (P < 0.05, ns) can be attributed to the well-known cytotoxicity of nanosilver. The increased cytotoxicity of the nanocomposite membranes upon irradiation may be due to the generation of ROS (data not shown). On the other hand, antiseptics, such as H2O2 (effective at concentrations above 3%), are widely used in clinical settings for the disinfection and treatment of wounds. Although H2O2 exhibits cytotoxicity, it is undoubtedly beneficial in chronic infected wounds where the tissue has already been damaged by infection; therefore, it outweighs any secondary damage. Similarly, Ag / TiO x Nanocomposite films are expected to have high therapeutic benefits when applied in medical devices.
Claims
1. A method for producing a composite layer in which photocatalytic nanoparticles are embedded in a polymer matrix, wherein the method comprises the following steps: a. Provide a substrate; b. generating photocatalytic nanoparticles in situ by flame spray pyrolysis and depositing the nanoparticles on the surface of the substrate via aerosol deposition to produce a photocatalytic nanoparticle film on the surface of the substrate; as well as c. immersing the photocatalytic nanoparticle film with a polymer solution or a liquid polymer precursor material to form the composite layer, Wherein, the photocatalytic nanoparticle film has a thickness of about 50 nm to about 5000 nm.
2. The method of claim 1, wherein the substrate is placed in the flow path of the flame at a distance of about 5 cm to about 100 cm.
3. The method of claim 1 or claim 2, wherein the substrate is placed in the flow path of the flame for a time of about 1 second to about 300 seconds.
4. A method according to any preceding claim, wherein the polymer solution or liquid polymer precursor material is applied to the nanoparticle film via spin coating, cast coating, slot coating, spray coating or dip coating.
5. The method according to any preceding claim, wherein the photocatalytic nanoparticles are titanium dioxide nanoparticles, silver-titanium nanoparticles, zinc oxide nanoparticles, iron-titanium oxide nanoparticles, copper-titanium oxide nanoparticles.
6. A method according to any preceding claim, wherein the photocatalytic nanoparticles have a size of about 5 nm to about 100 nm.
7. A method according to any preceding claim, wherein the nanoparticle film has a porosity of about 60% to 98% prior to adding the polymer solution.
8. The method according to any preceding claim, wherein the substrate is composed of a material selected from the list consisting of glass, ceramic, plastic, cross-linked elastomer and mixtures thereof.
9. A method according to any preceding claim, wherein the polymer in the liquid polymer solution or the liquid polymer precursor material is a water-insoluble polymer optionally selected from the list consisting of poly(dimethylsiloxane) (PDMS), poly(urethane), poly(methyl methacrylate) (PMMA), poly(ethylene), poly(propylene), poly(lactic-co-glycolic acid) (PLGA) and mixtures thereof.
10. A composite layer produced or obtainable using the method according to any one of claims 1 to 9.
11. A composite layer comprising a percolating network of photocatalytic nanoparticles in a polymer matrix, wherein the composite layer has a thickness of about 50 nm to about 5000 nm.
12. The composite layer according to claim 10 or claim 11, wherein the composite layer comprises two layers, namely a lower layer comprising the photocatalytic nanoparticles and an upper layer in which no nanoparticles are present.
13. The composite layer of claim 12, wherein the upper layer has a thickness of no greater than about 440 nm, such as about 50 μm to 440 nm, for example about 50 μm to 360 nm.
14. The composite layer of any one of claims 10 to 13, wherein the photocatalytic nanoparticles are present in an amount of about 2% to about 40% by volume of the composite layer.
15. A composite layer according to any one of claims 10 to 14, wherein the layer is deposited on a substrate.
16. The composite layer of claim 15, wherein the substrate is comprised of a material selected from the list consisting of glass, ceramic, plastic, cross-linked elastomer, and mixtures thereof.
17. A composite layer according to claim 15 or claim 16, wherein the substrate is a peelable backing layer.
18. An article coated with a composite layer according to any one of claims 10 to 17.
19. The article of claim 18, wherein the article is a medical device, such as a medical tube (e.g., a catheter or endotracheal tube), a microneedle device, a wound dressing, or a high-frequency contact object, such as a light-emitting display panel or a handrail.
20. Use of a composite layer as claimed in any one of claims 10 to 17 for providing photocatalytic disinfecting properties to a surface.
21. A method of treating and / or preventing bacterial infections via the use of a composite layer according to any one of claims 10 to 17.